‘Enhancing natural beauty’ or ‘poems thrust in my face’?: perceptions of artworks in ‘wild’ landscape settings - Porter, Nicole (2015)
What role can (or should) artworks play in non-urban landscapes, particularly those perceived as ‘wild’? Conceptions of natural landscapes are a part of cultural discourse, and consequently artworks can both reflect and affect concepts of wilderness. Site-specific artworks situated in remote settings offer particular opportunities for interpreting relationships between culture and nature, time and place, and can communicate a range of environmental and social values. However, art can be controversial, and artworks in protected and sensitive landscapes more so. How does a contemporary cultural artefact impact the experience and understanding of ‘wild’ landscapes, especially if the people drawn to such landscapes value their timeless and non-human qualities? Can cultural expressions and wild places co-exist?